Modeling Ca2+ signals: understanding Ca2+ regulatory networks in cells - Ca2+ stores: endoplasmic reticulum, calcium oscillations - Friel, David (Henry Stewart Talks, 2021)
Qualitative properties of Ca2+ dynamics, Steady states, The impact of Ca2+ stores on Ca2+ signals, Ca2+ sources and sinks, The linear one-pool model, Nullclines, Ca2+ induced Ca2+ release (CICR), Ca2+ oscillatory cycles, The nonlinear model